2015
DOI: 10.1016/j.marpolbul.2015.09.013
|View full text |Cite
|
Sign up to set email alerts
|

Experimental assessment of critical anthropogenic sediment burial in eelgrass Zostera marina

Abstract: Seagrass meadows, one of the world's most important and productive coastal habitats, are threatened by a range of anthropogenic actions. Burial of seagrass plants due to coastal activities is one important anthropogenic pressure leading to the decline of local populations. In our study, we assessed the response of eelgrass Zostera marina to sediment burial from physiological, morphological, and population parameters. In a full factorial field experiment, burial level (5-20cm) and burial duration (4-16weeks) we… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…Many available sites for restoration efforts are in exposed and typically high sediment load, and therefore accreting, environments (e.g., [ 35 , 44 45 ]); concomitantly, seagrasses create an accreting ecosystem (e.g., [ 46 ]). Therefore, the rate and duration of burial is potentially a significant determinant of restoration success, particularly if the resilience to burial varies between species or transplant unit types (e.g., [ 14 , 28 , 47 ]). This study found that resilience to burial duration for Posidonia australis varied between transplant unit types.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Many available sites for restoration efforts are in exposed and typically high sediment load, and therefore accreting, environments (e.g., [ 35 , 44 45 ]); concomitantly, seagrasses create an accreting ecosystem (e.g., [ 46 ]). Therefore, the rate and duration of burial is potentially a significant determinant of restoration success, particularly if the resilience to burial varies between species or transplant unit types (e.g., [ 14 , 28 , 47 ]). This study found that resilience to burial duration for Posidonia australis varied between transplant unit types.…”
Section: Discussionmentioning
confidence: 99%
“…Successful transplantation and restoration (or rehabilitation) of seagrass rely upon knowledge of the target species’ autecological requirements to determine the appropriate transplant unit type [ 5 , 6 ] and appropriate recipient site [ 5 ], including understanding if site specific stressors that led to seagrass decline have been ameliorated or removed. Equally important is the knowledge of how the species responds to disturbance events such as sediment burial, intensity of herbivory, and changing nutrient levels (e.g., [ 7 14 ]). Consequently, restoration and rehabilitation success may be heavily influenced by disturbance at a proposed transplant site.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Living under threat for at least a century, seagrasses may be nearing a crisis in terms of their global sustainability (Orth et al , ; Waycott et al , ). Reductions in water quality (Munkes et al , ), higher water temperatures (Greve et al , ; Reusch et al , ) and climate variability (e.g. summer heat waves; Ehlers et al , ; Bergmann et al , ; Winters et al , ) have all been identified as major threats to seagrass meadows (reviewed by Orth et al , ; Björk et al , ; Waycott et al , ).…”
Section: Introductionmentioning
confidence: 99%